2019
DOI: 10.5935/1518-0557.20190050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GnRH analogues for pituitary suppression on oocyte morphology in repeated ovarian stimulation cycles

Abstract: Objective: To compare the effect of pituitary suppression regimens on oocyte morphology in consecutive ICSI cycles of the same patients. Methods: Data was obtained from 200 matched consecutive intracytoplasmic sperm injection (ICSI) cycles performed in 100 couples undergoing the first cycle with the GnRH agonist and the following cycle with the GnRH antagonist regimen, from January 2010 to August 2016, in a private university-affiliated IVF centre. The effects of the pituitary suppression type on oocyte morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…We also agreed with the result of the retrospective study of Rienzi et al [49], in which the author compared the effect of three different controlled ovarian stimulation protocols; GnRH agonist Long protocol (268 cycles), GnRH antagonist protocol (142 cycles), and natural cycle with minimal stimulation (106 cycles), but could not detect any correlation between oocyte morphology, and the type of protocol used [49]. However, our results disagreed with other study results [39,47,50]. The studies of Ebner et al [47] and Murber et al [50] have reported worse oocyte morphology in the GnRH antagonist group, with lower zona scores [47] and higher rates of cytoplasmic dysmorphisms [50].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…We also agreed with the result of the retrospective study of Rienzi et al [49], in which the author compared the effect of three different controlled ovarian stimulation protocols; GnRH agonist Long protocol (268 cycles), GnRH antagonist protocol (142 cycles), and natural cycle with minimal stimulation (106 cycles), but could not detect any correlation between oocyte morphology, and the type of protocol used [49]. However, our results disagreed with other study results [39,47,50]. The studies of Ebner et al [47] and Murber et al [50] have reported worse oocyte morphology in the GnRH antagonist group, with lower zona scores [47] and higher rates of cytoplasmic dysmorphisms [50].…”
Section: Discussionsupporting
confidence: 77%
“…Typically, the oocyte quality is determined based on the nuclear maturation status and the presence of certain extra and intracytoplasmic morphologic features [39]. Although the impact of oocyte morphology on embryo competence and cycle outcomes is still controversial [40][41][42][43][44][45], evaluating the morphological characteristics of the oocytes after being denudated is considered a routine step during the ICSI process; in an attempt to improve the chance of obtaining and transferring embryos with a better implantation potential.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…SER+ in the cytoplasm of oocytes is also correlated with E2 on the hCG-treatment day: the higher the peripheral blood E2 concentration, the more likely it is for SER+ to materialize [ 28 ]. Oocyte SER+ may also be caused by overstimulation of the ovaries [ 29 ]; for example, increasing GnRH and prolonging the duration of ovarian stimulation increases SER+ [ 3 , 6 , 30 ]. Maternal age and FSH dose are unrelated to the appearance of SER+, although follicle stimulation and oocyte collection significantly increase its risk [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Total fertilization failure (TFF) occurs in 1–5% of ICSI cases ( Kyono et al , 2012 ; Montag et al , 2012 ; Vanden Meerschaut et al , 2014b ; Kashir et al , 2018 ; Basirat et al , 2019 ; Bassiri et al , 2020 ). Moreover, associations have been identified between embryo grading and congenital malformations, endocrine profile changes and deficient hearing in ICSI-conceived babies ( Abel et al , 2019 ; Belva et al , 2019 ; Yasemin Sert et al , 2019), while age, antimullerian hormone levels and antral follicle counts are associated with live birth rates following ICSI, with other hormones currently under investigation ( Metello et al , 2019 ; Zheng et al , 2019 ; Song et al , 2020 ; Tarín et al , 2020 ; Tiegs et al , 2020 ; Wang et al , 2020 ; Ye et al , 2020 ; Zanetti et al , 2020 ). The use of ART however does not seem linked to an increase in the risk of autism spectrum disorder or preeclampsia ( Diop et al , 2019 ; Kennedy et al , 2019 ).…”
Section: Introductionmentioning
confidence: 99%